2014
DOI: 10.2527/jas.2013-6979
|View full text |Cite
|
Sign up to set email alerts
|

A disparate trace element metabolism in zebu (Bos indicus) and crossbred (Bos indicus × Bos taurus) cattle in response to a copper-deficient diet1

Abstract: Copper deficiency is a commonly diagnosed problem in cattle around the globe. In Jimma, Ethiopia, 8 zebu (Bos indicus) and 8 zebu × Holstein Friesian cross (Bos taurus × Bos indicus) heifers were used in an 11-wk study to investigate breed type differences and effects of Cu deficiency on concentrations of trace elements in plasma and edible tissues as well as mRNA expression of Cu-related genes. Heifers were fed a grass diet (6.4 ± 0.2 [SEM] mg Cu/kg DM) supplemented with 1 mg Mo/kg DM in wk 1 to 4 and 2 mg Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…The trace element supply for zebu-influenced cattle in the Gilgel Gibe catchment, Ethiopia, was imbalanced (Dermauw et al, 2013b(Dermauw et al, , 2014b, based on the comparison of dietary trace element levels with reported requirements for cattle. However, the applicability of these reported Bos taurus requirements for zebu cattle was not investigated yet.…”
Section: Results and Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…The trace element supply for zebu-influenced cattle in the Gilgel Gibe catchment, Ethiopia, was imbalanced (Dermauw et al, 2013b(Dermauw et al, , 2014b, based on the comparison of dietary trace element levels with reported requirements for cattle. However, the applicability of these reported Bos taurus requirements for zebu cattle was not investigated yet.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…More research is needed to fully unravel the extent of the impact of these factors, particularly in zebu cattle. Moreover, the potential difference in trace element metabolism between different types (Bos indicus vs. Bos indicus x Bos taurus) of cattle (Dermauw et al, 2014b) requires extra attention, as it might have a large impact on the optimal nutritional management of these animals.…”
Section: Results and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also increases the structural strength of connective tissues and blood vessels, and strength of horns and hooves. Deficiencies of Cu have been associated with retained placenta, embryonic death and decreased conception rates and anoestrus (8). Copper deficiency is also associated with depressed oestrus, silent heats and reduced conception rate (21).…”
Section: Effect Of Mineralsmentioning
confidence: 99%
“…The response of erythrocyte CCS protein expression is interesting, as collection of a blood sample is much easier than liver collection, and ease of sample collection is a hallmark of a good biomarker. Interestingly, in both Bos Indicus and Bos Taurus steers fed low Cu diets (6.4 mg Cu and 1 mg Mo/ kg diet DM) for 11 wk with an average final liver Cu of approximately 25 mg/kg diet DM, there was a positive correlation found between liver Cu and liver CCS mRNA expression (r = 0.58; Dermauw et al, 2014). Generally, CCS is increased during Cu deficiency, likely due to the increased need for CCS to scavenge Cu if there is a larger quantity available (Bertinato et al, 2003).…”
Section: Copper Biomarkersmentioning
confidence: 98%